Makna Leksikal dan Makna Kultural yang Terdapat Pada Ornamen Rumah Majapahit Desa Bejijong : Kajian Etnolinguistik - Arni Yuniar Prastika; Muhitotun Nadhifah; Taswirul Afkar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In this research, the researcher's aim is to find out the lexical and cultural meaning of the ornaments in the Majapahit nuanced house ornaments in Bejijong village. This research method uses descriptive qualitative. The data from this research is in the form of a term for a house ornament with a Majapahit nuance, which was obtained from an article that was read. The technique that researchers use in collecting data is: collecting data from interview and then we process and research it using ethnolinguistic studies, namely looking for lexical meaning and cultural meaning. Then, after finding the data, the researcher will use a data analysis technique, namely data classification, data description and finally drawing conclusions. The result of this research is to find out a meaning, namely an ethnolinguistic study in the form of lexical meaning and cultural meaning in the Majapahit house in Bejijong village.